EDUKASI PERAN REMAJA MENGGUNAKAN VIDEO ANIMASI DALAM PENCEGAHAN TUBERCULOSIS PARU PADA SANTRI PONDOK PESANTREN - Anandhita, Aries Chandra; Mukarromah, Nur; Marini, Gita; Asri, Asri; Husna, Anis Rosyiatul; Priyantini, Diah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Pulmonary tuberculosis (TB) is one of the infectious diseases that is still a significant global health problem, including in Indonesia. Adolescents, as the dominant age group in Islamic boarding schools, have great potential to play an active role in efforts to prevent pulmonary tuberculosis (TB). Education is needed with effective media that is in accordance with the times. The purpose of community service is to evaluate the effectiveness of education on the role of adolescents through animated videos in preventing pulmonary tuberculosis. This community service activity was carried out using the method of compiling educational materials in the form of animated videos, selecting participants from Islamic boarding school students as many as 80 female adolescents, implementing educational sessions using animated videos, interactive discussions and questions and answers and evaluating participant understanding through pre-test and post-test questionnaires. The results of the community service showed an increase in knowledge. There was an increase in the average knowledge score of 35% after the animated video intervention. Changes in attitude showed that 78% of respondents showed a more positive attitude towards preventing pulmonary tuberculosis. Increased awareness showed that 82% of students reported increased awareness of the importance of preventing pulmonary tuberculosis. The use of animated videos is effective in increasing the knowledge and role of adolescent Islamic boarding school students in preventing pulmonary tuberculosis.